Strategic performance measurement system, organizational learning and service strategic alignment: Impact on performance. Issue 4 (12th November 2018) - Yuliansyah, Yuliansyah; Jermias, Johnny
Abstract : Purpose: Considering the significant contribution of service sector of the whole contribution of the economics, this study aims to investigate the impact of strategic performance measurement sytstem (SPMS) on sustainability strategic outcomes in the industry through organizational learning and service strategic alignment. Design/methodology/approach: Using a survey study, 158 usable data were analysed using SmartPLS. Findings: The results show that service strategic alignment and organizational learning mediate the relationship between SPMS and performance for product differentiation companies. For cost leadership companies, the results indicate that there is no mediation of service strategic alignment and organizational learning on the relationship between SPMS and performance. Research limitations/implications: This study first provides evidence that SPMS improves performance through service strategic alignment and organizational learning for product differentiation companies in which innovation is crucial to thrive and succeed. Second, it introduces to the literature the characteristics of SPMS. Originality/value: New insights of implementation of SPMS in improving companies' performance in Indonesian financial institutions are provided.